Defining required forest area for protection soil from erosion in Vietnam: a GIS-based application - Bao, Tran Quang; Melinda, Laituri J. (VNU Journal of Science: Earth and Environmental Sciences; Vol 27 No 2, 2011)
Abstract. Forests play an important role in reducing erosion. In Vietnam, destroying natural forests in mountainous areas has caused serious environmental problems for sustainable development. Required forest areas for protection of soils from erosion in Vietnam are defined in this study. An algorithm of defining required forest area for soil erosion prevention is based on a comparison of soil loss prediction and its threshold of 10 ton ha -1 yr -1 (soil loss tolerance) within the GIS environment. Soil loss is predicted from rainfall erosivity index, slope, porosity and vegetation structures in which rainfall index is calculated from 30 year monthly rainfall data of 158 weather stations. A map of erosion risk for Vietnam illustrating potential to erode soil was generated from slope, rainfall index and soil porosity by using spatial interpolation and map algebra techniques in ArcGIS. Vegetation index, a function of canopy closure, height, ground cover and litter cover, is classified into four groups. Required forest areas for protection of soil from erosion are defined from an erosion risk map in comparison with categories of vegetation index. An area (a raster cell) requires forest (natural forest or the others) when its erosion risk is higher than the vegetation index. Keywords: Soil Erosion, GIS, Required Forest Area, Erosion Risk Map, Soil Loss.